Physicochemical Properties and Antibacterial Activity of Kaffir Lime Oil Emulsion Applicable to Baverage Product - Windrayan Pambudi, Vincentius Johar; Iftitah, Elvina Dhiaul; Mardiana, Diah (Indonesian Green Technology Journal, 2022)
Essential oil inside beverage emulsion became an interesting subject to get a new value for the fast-moving customer goods (FMCG) market. In this study, kaffir lime oil (KFO) antibacterial test on formulation and physicochemical properties of kaffir lime oil in water beverage emulsions was investigated. The main ingredients of beverage emulsions are water, high fructose corn syrup (HFCS), Arabic gum as an emulsifier, vitamin E, and kaffir lime oil as flavoring and antibacterial. KFO composition used instrument with Stability of oil-in-water emulsion was observed by measuring physicochemical properties: turbidity, alkalinity, and conductivity. GC-MS characterization on kaffir lime essential oils revealed the top three components, i.e., citronella (46,47%), citronellol (12,22%), and citronellyl acetate (6,48%). FT-IR KFO spectrum had absorbance at 1726 (C=O stretching), 2922, and 2874 cm-1 (C-H stretching from aldehyde). Absorbance was also present on 1454 and 1379 cm-1 (C=C stretching) wavelengths, resembling citronella. Gum arabic with R−S(=O)₂−OH  group addition reduced pH value to 1.1 on each composition addition and increased conductivity by 317.3 μS/cm. Fructose addition reduced the value by 153.4 μS/cm. Turbidity value increased averagely by 46,9 NTU, then reduced by 14,4 NTU. Citronellal in KFO could hinder e-coli bacterial growth and had an alt value >72 CFU/mL. This formulation study produces a beverage product with pH, conductivity, and turbidity values following the standard and has criteria under the microbiological contamination limit of BPOM and SNI standards. Keywords: emulsified beverage, kaffir lime oil, physicochemical properties, stability, perception